2022
DOI: 10.1186/s40104-022-00725-z
|View full text |Cite
|
Sign up to set email alerts
|

A plant-based diet supplemented with Hermetia illucens alone or in combination with poultry by-product meal: one step closer to sustainable aquafeeds for European seabass

Abstract: Background Increasing demand for high-value fish species and pressure on forage fish is challenging aquaculture to ensure sustainable growth by replacing protein sources in aquafeeds with plant and terrestrial animal proteins, without compromising the economic value and quality of the final fish product. In the present study, the effects of a plant protein-based diet (CV), two plant-based diets in which graded amounts of plan protein mixtures were replaced with Hermetia illucens meal alone (VH1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 128 publications
(127 reference statements)
1
7
0
Order By: Relevance
“…Several authors have reported that lipid peroxidation affects long-chain PUFAs [23,51,52]; however, in the present study, the different dietary treatments had not effect on this parameter, since low levels of lipid oxidation were measured in fish muscle (0.7 mg MDA/kg) in all the experimental groups, values that were within the range of perfect quality fish for human consumption [53]. In addition, skin coloration plays an important role in consumer acceptance of farmed fish, with intense skin coloration usually associated with high-quality products [54]. Skin pigmentation is influenced by a wide variety of factors such as genetic, environmental, physiological, dietary, and others [54,55].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several authors have reported that lipid peroxidation affects long-chain PUFAs [23,51,52]; however, in the present study, the different dietary treatments had not effect on this parameter, since low levels of lipid oxidation were measured in fish muscle (0.7 mg MDA/kg) in all the experimental groups, values that were within the range of perfect quality fish for human consumption [53]. In addition, skin coloration plays an important role in consumer acceptance of farmed fish, with intense skin coloration usually associated with high-quality products [54]. Skin pigmentation is influenced by a wide variety of factors such as genetic, environmental, physiological, dietary, and others [54,55].…”
Section: Discussionmentioning
confidence: 84%
“…In addition, skin coloration plays an important role in consumer acceptance of farmed fish, with intense skin coloration usually associated with high-quality products [54]. Skin pigmentation is influenced by a wide variety of factors such as genetic, environmental, physiological, dietary, and others [54,55]. In the present study, significant differences were obtained in the parameter a * in fish fed the 2,000F compared to control, though a general trend to show a greenish skin appeared in all the group fed diets supplemented with phytase and microalgae.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, up to 45% of HPM can successfully replace FM in diets for European seabass juveniles without impairing growth, feed utilization, and digestibility [ 65 ]. Furthermore, Pleic et al [ 26 ] recently demonstrated that, in diets deprived of FM, the replacement of plant-derived ingredients with defatted HPM, alone or in combination with poultry by-product meal, significantly improved the growth performance and led to positive effects on intestinal digestive/absorptive functions and microbial communities in European seabass subadults.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HPM is rich in bioactive molecules such as chitin, lauric acid, and antimicrobial peptides, which have been reported to have immunostimulatory and anti-inflammatory effects on fish gut [ 16 ]. Nevertheless, the HPM fatty acid profile does not meet the fish nutritional requirements, lacking in long-chain polyunsaturated fatty acids (PUFA), such as EPA and DHA, which raises serious concerns about the use of full-fat HPM in feed formulations, especially for marine fish species [ 25 , 26 ]. For this reason, several studies have been conducted with defatted HPM in both marine and freshwater fish species [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, only a few research studies have evaluated the partial replacement of plant protein-rich feeds with insect and poultry by-product meals, singly or combined, in low-fish meal diets for sea bream [42,43] and sea bass [44]. These studies mostly investigated the dietary effects on appetite, growth performance, gut health, and fish quality, while fish response in terms of liver health status has received limited attention.…”
Section: Introductionmentioning
confidence: 99%